Hypertensive Disorders of Pregnancy and Offspring Cardiac Structure and Function in Adolescence. Issue 11 (November 2016) - Timpka, Simon; Macdonald‐Wallis, Corrie; Hughes, Alun D.; Chaturvedi, Nishi; Franks, Paul W.; Lawlor, Debbie A.; Fraser, Abigail
Abstract : Background: Fetal exposure to preeclampsia is associated with higher blood pressure and later risk of stroke. We aimed to investigate the associations of maternal preeclampsia, gestational hypertension, and maternal blood pressure change in pregnancy with offspring cardiac structure and function in adolescence. Methods and Results: Using data from a prospective birth cohort study, we included offspring who underwent echocardiography (mean age, 17.7 years; SD, 0.3; N=1592). We examined whether hypertensive disorders of pregnancy were associated with offspring cardiac structure and systolic/diastolic function using linear regression. Using multilevel linear spline models (measurement occasions within women), we also investigated whether rate of maternal systolic/diastolic blood pressure change during pregnancy (weeks 8–18, 18–30, 30–36, and 36 or more) were associated with offspring outcomes. Main models were typically adjusted for maternal age, offspring age and sex, prepregnancy body mass index, parity, glycosuria/diabetes mellitus, education, and maternal smoking. Exposure to maternal preeclampsia (0.025; 95% CI, 0.008–0.043) and gestational hypertension (0.010; 0.002–0.017) were associated with greater relative wall thickness. Furthermore, preeclampsia was also associated with a smaller left ventricular end‐diastolic volume (−9.0 mL; −15 to −3.1). No associations were found between hypertensive disorders of pregnancy and offspring cardiac function. Positive rate of maternal systolic blood pressure change during weeks 8 to 18 was associated with greater offspring left ventricular end‐diastolic volume, left ventricular mass indexed to height 2.7, and E/A. Conclusions: Adolescent offspring exposed to maternal preeclampsia had greater relative wall thickness and reduced left ventricular end‐diastolic volume, which could be early signs of concentric remodeling and affect future cardiac function as well as risk of cardiovascular disease.